2003
DOI: 10.1038/sj.leu.2402999
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of the myeloid differentiation antigen CD65s, a feature of poorly differentiated AML in older adults: study of 711 patients enrolled in ECOG trials

Abstract: CD65s appears when the progenitor antigen CD34 disappears, suggesting that this sialylated carbohydrate antigen marks a turning point in normal myeloid differentiation. We characterized acute myeloid leukemia (AML) with low CD65s expression (CD65s low AML) in 711 patients entered on seven Eastern Cooperative Oncology Group AML treatment trials (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999). Of those, 198 (28%) qualified as having CD65s low AML. Morphologically, CD65s low A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The relatively good prognosis and responsiveness to lenalidomide therapy of del(5q) MDS patients 49 are in agreement with the superior outcome of differentiated, CD65 ϩ AML. 30 Accumulating data in MDS indicate that fatigue and transfusion dependence negatively impact patients' QOL. 12,17,50 In our study, we demonstrated no differences in fatigue and QOL subscale scores between treatment groups (EPO vs SC) at 4 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively good prognosis and responsiveness to lenalidomide therapy of del(5q) MDS patients 49 are in agreement with the superior outcome of differentiated, CD65 ϩ AML. 30 Accumulating data in MDS indicate that fatigue and transfusion dependence negatively impact patients' QOL. 12,17,50 In our study, we demonstrated no differences in fatigue and QOL subscale scores between treatment groups (EPO vs SC) at 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…29 ECOG has used CD65s expression to differentiate between undifferentiated (Յ 30% CD65 ϩ myeloblasts) from differentiated AML (Ͼ 30% CD65 ϩ myeloblasts). 30 …”
Section: Flow Cytometrymentioning
confidence: 99%
“…Multivariate predictors for disease resistance include cytogenetics, beta-2 microglobulin and PS (Albitar et al, 2007;Estey, 2008), and for OS include cytogenetics, age, luekocytosis, LDH, CD34-expression and NPM1 status (Rollig et al, 2010). More blasts at diagnosis predicted worse outcomes (Baudard et al, 1994), as did CD34-positive disease (Rollig et al, 2010), the presence of chromosomal monosomies (Breems et al, 2008;Medeiros et al, 2010), decreased expression of CD65s (Paietta et al, 2003) and increased expression of CD7 (Stasi et al, 1996). Interestingly, age is not a multivariate predictor of outcomes in several models (Chen et al, 2005;Gupta et al, 2005a;Malfuson et al, 2008), suggesting other risk factors may be more important for treatment decisions.…”
Section: Other Prognostic Factorsmentioning
confidence: 99%
“…The presence of a distinct CD25 POS myeloblast population (range, 19%-99%) defined CD25 positivity (CD25 POS ). Undifferentiated, CD65 (s) LOW , 30 and CD11b POS AML were characterized as previously reported. 31 …”
Section: Flow Cytometric Determination Of Cd25 and Other Stem Cell Anmentioning
confidence: 99%